Safety Profile of Using Ciprofloxacin in Paediatrics: A Systematic Review and Meta-Analysis - Baraneh Masoumi; Gohar Eslami; Reza Alizadeh-Navaei; Pritish Mondal; Mohammad Sadegh Rezai (Mazandaran University of Medical Sciences, 2019)
Context: The use of ciprofloxacin is contraindicated in children due to safety concerns. Animal studies have revealed that ciprofloxacin can be associated with arthropathy (joint toxicity) in juvenile animals; however, this potential side effect has not been proven in children. Many clinicians still prescribe ciprofloxacin when there is no suitable alternative. In many developing countries, access to the newer generation of antibiotics is either limited or expensive. Therefore, ciprofloxacin is an available and cost-effective alternative that can save lives when necessary. Objective: This study aimed to systemically review the published studies about the safety profile of using ciprofloxacin in children. Data Sources: All relevant studies published from 1990 to 2018 in the Cochrane library, Trip database, ScienceDirect, PubMed, and Google Scholar were collected. Study Selection: We have only considered clinical trials, which included the following keywords: "ciprofloxacin", "children under 18 years", and "arthropathy".  Data Extraction: The collected data were analyzed by Comprehensive Meta-Analysis software (CMA.2). We used random or fixed-effect methods based on the heterogeneity of the results. The heterogeneity was checked by I2 index and tau-squared. The publication bias was evaluated by the Begg's test. Results: The obtained data indicated no increased risk of arthropathy after ciprofloxacin use in children on a short-term basis, in comparison to placebo or other antibiotics. Conclusions: Ciprofloxacin is potentially a safe alternative to be used in children under 18 years old when there is no better alternative.